Materials of the Girs Revision as a Source on the Financial Situation of Turkestan of the XIX Century - Pustovaya Elena Sergeevna (International Journal on Integrated Education, 2022)
The article analyzes the economic situation and financial condition of the Turkestan region, compiled in 1882 - 1884 based on the materials of the revision of the Privy Councilor F. Girs